Altered functional connectivity of the thalamus in patients with insomnia disorder after transcutaneous auricular vagus nerve stimulation therapy - Zhao, Bin; Bi, Yanzhi; Chen, Yong; Zhang, Jinling; Zhang, Shuai; Zhang, Dongshu; Rong, Peijing (Frontiers in Neurology, 2023)
The pathogenesis of insomnia is related to the dysfunction of thalamus. Transcutaneous auricular vagus nerve stimulation (taVNS) proved to be effective in treating insomnia. However, whether taVNS alleviates insomnia through modulating thalamus-related functional connectivity remains unclear. To elucidate the instant modulating effects of taVNS on resting state functional connectivity (RSFC) of thalamus, twenty patients with primary insomnia (PI) were recruited to receive taVNS treatment and their resting state functional magnetic resonance imaging (fMRI) data were collected immediately before and after stimulation. The fMRI data were compared with age and gender matched 20 healthy subjects who received no stimulation with RSFC fMRI data collected once. RSFC analyses of thalamus were performed in both groups. In addition to assessing the group differences between PI patients and healthy controls on RSFC of thalamus, we examined the taVNS-induced changes of RSFC of thalamus in PI patients. Before taVNS treatment, PI patients showed increased RSFC of thalamus with right insula, superior temporal gyrus, superior limbal gyrus, inferior frontal gyrus, and left insula than healthy controls. After taVNS treatment, the RSFC between thalamus and left insula in PI patients was decreased in comparison with healthy controls. After taVNS treatment, RSFC between the thalamus and right angular gyrus, left superior frontal gyrus, right middle frontal gyrus, right superior marginal gyrus, anterior cingulate gyrus, precuneus, right insula, right superior temporal gyrus, right middle temporal gyrus, and right putamen were significantly decreased in PI patients. This study provides insights into the instant brain effects involving thalamus-related functional connectivity of taVNS on PI patients.